STRATEGI MANAJEMEN KAS (CASH MANAGEMENT) DALAM RANGKA OPTIMALISASI DANA PADA YAYASAN INSAN MADANI SEJAHTERA (YIMS) TAHUN 2004-2009 - Anwar, Yuli (STIE Binaniaga, 2012)
cash management strategy (cash management) in order to optimize the foundation fund civil insan prosper (yims) year 2004-2009. Cash management strategy (cash management) in order to optimize the funds on Madani Insan Sejahtera Foundation (Yims) include: revenue from the year 2004 amounting to Rp. 18,250,500.00 until 2009 to Rp. 559,454,000.00 or 300 times increase. Similarly, expenditure in the form of compensation, public health services, skills training, caring teachers and preachers, the economic empowerment of the ummah, qurban from 2004 amounting to Rp. 17,787,500.00 until 2009 to Rp. 559 005 100 is almost 300%. The channeling of funds up to 98% - 102% from 2004 to 2009. The remaining funds are used for operational reserves the foundation. The Foundation expects an increase in revenue from activities that are funded in accordance mission of the foundation is: (1) to provide services to the community through empowerment programs that integrate educational programs, health, economy and skills. (2) Being a liaison between the haves with the community through the distribution of funds can not afford the social, charity, infaq, shodaqoh and humanitarian funds. (3) Establish partnerships with both private institutions, government or other social institutions in reducing social problems in the community. Keywords : cash management